FACTORS ASSOCIATED WITH PREVALENCE OF SURGICAL SITE INFECTION AMONG POSTOPERATIVE PATIENTS ON THE SURGICAL WARD AT HOIMA REGIONAL REFERRAL HOSPITAL. - KYAMULESIRE , CANTIGEN; NAMUTEBI , FLORENCE (Student’s Journal of Health Research Africa, 2023)
Background: Surgical site infections refer to infections occurring up to 30 days after surgery and affecting either the incision or deep tissue at the incision site. This study was conducted to assess the prevalence of surgical site infection among postoperative patients in the surgical ward at Hoima Regional Referral Hospital. Methodology: A descriptive cross-sectional study design employed quantitative methods of data collection. 50 respondents (postoperative patients) were obtained by simple random sampling technique. Convenient sampling was also employed to select 20 nurses to participate in the study. Results: This study established that 7(14%) of the participants had developed surgical site infection, 3(42.9%) of those suffering from diabetes, 1(14.2%) required minimal assistance, 3(42.8%) required moderate assistance and 3(42.9%) required significant assistance, 1(14.3%) was aged less than 20 years, 2(28.9%) were in the 40-49 age group while 4(57.1%) were aged 50 years or greater while none of them smoked or had a history of smoking. Out of the 7 patients with SSI, 5(71.4%) had emergency surgeries, and 2(28.6%) had elective surgeries. 5(71.4%) did not have their operation site shaved before surgery while 2(28.4%) had shaved. 3(42.9%) of 7 patients with SSI had an operation duration between 1-3hours while 4(51.9%) had a duration of greater than 3 hours. 3(42.9%) had a postoperative stay between 7-14 days while 4(57.1%) had had an operative stay greater than 14 days. Conclusion. There was a 14% prevalence of surgical site infection related to illnesses such as diabetes, patient dependence and age 40 years or greater, healthcare factors, emergency surgery, abdominal surgery, not shaving the operation site, operation duration 1 hour or greater and postoperative stay 7 days or more. Recommendations: The staff of Hoima Regional Referral Hospital, particularly in the surgical department should strengthen preoperative care given to patients before surgery especially those undergoing abdominal surgeries